2020
DOI: 10.1530/eje-20-0150
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of endocrine autoimmunity in first-degree relatives of patients with autoimmune Addison’s disease

Abstract: Objective Autoimmune conditions tend to cluster in subjects with Addison’s disease (AD) and probably also among their relatives. The aim of the study was to estimate the frequency of the endocrine gland-specific autoantibodies in first-degree relatives of patients with AD. Methods Autoantibodies were investigated in 113 family members using RIA and ELISA assays. The control group comprised 143 age-matched volunteers. Results Autoimmune diseases were diagnosed in 38.1% relatives. Hashimoto’s thyroiditis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Apart from aTPO, which was more prevalent in females, no sex-related differences nor predisposition connected with relationship to the patient (parents, siblings, or offspring) were noted. However, as in previous analysis, relatives of the male AD patients, and of those suffering from polyendocrine autoimmunity appeared most prone to develop autoantibodies (9).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Apart from aTPO, which was more prevalent in females, no sex-related differences nor predisposition connected with relationship to the patient (parents, siblings, or offspring) were noted. However, as in previous analysis, relatives of the male AD patients, and of those suffering from polyendocrine autoimmunity appeared most prone to develop autoantibodies (9).…”
Section: Discussionsupporting
confidence: 76%
“…Our former study revealed that nearly 40% first-degree relatives of the AD patients displayed circulating serum autoantibodies to the endocrine gland-specific antigens compared to just 8.4% subjects with no family history of autoimmunity (9). Familial incidence of the autoimmune disease might be partially due to similar environmental exposures, but high concordance rates in monozygotic twins support substantial role of the genetic factors associated with the incidence of T1D, AD and autoimmune thyroid disease (AITD) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…A family history of AD was reported in 10% of the Norwegian patients and 6% of the Swedish ones (1,3). A small case-control study from Poland reported that 3% of the family members were also diagnosed with AD and that thyroid AID was found in almost 30% of the family members (6). In our previous family studies, AD was associated with type 1 diabetes and Graves disease in family members (7,8).…”
Section: Introductionmentioning
confidence: 79%
“…Family studies on AD are rare and include the recent small hospital-based study from Poland and twin studies from Sweden, discussed in Introduction (6,11,12). However earlier studies on other AIDs have observed significant associations with AD in family members, including studies on vitiligo, thyroid diseases and multiple sclerosis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In most instances, the etiology of these disorders remains obscure and combines some poorly determined environmental triggers with complex inherited susceptibility, conferred by numerous genetic polymorphisms [ 2 ]. Autoimmune conditions tend to cluster within families, although their inheritance pattern is rarely straightforward [ 3 , 4 ]. Furthermore, genetically predisposed individuals may develop several autoimmune diseases, traditionally categorized into four distinct autoimmune polyendocrine syndromes (APS) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%